Attendance policies on university language degrees: exploring attitudes, and measuring relationships with performance and progression. Issue 7 (8th August 2020) - Bruen, Jennifer; Kelly, Niamh; Loftus, Maria
ABSTRACT: This paper explores the attitudes of undergraduate language learners and their lecturers towards the introduction of an attendance policy in an Irish Higher Education Institution. It also analyses the relationship between the introduction of this policy and student performance (average grade) and progression (pass rates). The policy was introduced on a pilot basis on thirty core language modules delivered on first or second year undergraduate programmes. They consisted of language modules in German (beginners and intermediate), French (intermediate), Spanish (beginners and intermediate), Chinese (beginners) and Japanese (beginners). The findings suggest predominantly positive attitudes towards the attendance policy among both staff and students. They also indicate a positive impact on performance and progression in some modules, in particular first year beginner languages where attendance has been an issue in the past. The paper considers the implications of these findings both for this field of research and for practitioners particularly in university language learning contexts.